The Rinau Case and the wrongful removal or retention of children - Gonçalves, Anabela Susana de Sousa (2014)
The Rinau Case is a landmark decision of the ECJ regarding the wrongful removal or retention of children in the Regulation 2201/2003 concerning jurisdiction and the recognition and enforcement of judgments both in matrimonial matters and those of parental responsibility (Brussels II bis). Having this case as starting point, this article explains the fast proceedings laid down in Brussels II bis Regulation for situations of wrongful removal or retention of children and the special rules for the recognition of the decision of return of the child wrongfully removed or retained in another Member State. However, as a preliminary point of discussion, and in order to allow a more comprehensive understanding of the proceedings concerning the wrongful removal or retention of children under the Regulation, a brief explanation of the framework of the regulation and the rules of international jurisdiction in matters of parental responsibility is provided.